KEMAMPUAN PENALARAN BERDASARKAN KEYAKINAN MATEMATIKA DALAM PEMBELAJARAN PBL MELALUI PENDEKATAN INTERAKSI DYADIC - Dyah Retno Kusumawardani (Jurusan Matematika FMIPA Universitas Jenderal Soedirman, 2018)
The purposes of this research were (1) to describe the learning quality of PBL through dyadic interaction approach to mathematical reasoning ability of grade X students of IT Al Irsyad Purwokerto High School (2) to find pattern of students reasoning ability based on mathematical belief. This study uses a mixed method. Data analysis started from the analysis of test items. The analysis uses the prerequisite test and then hypothesis testing uses rara average (t-test), then the proportion of comparative tests (test-z) is to calculate the classical completeness. Further testing of determining the difference between the two classes uses different test average (t-test right side). Qualitative data analysis uses qualitative description. The results of quantitative research shows that learning class with PBL and dyadic interaction approach reached classical total 80%. The average difference test showed class’ results with PBL dyadic interaction approach better than a class activity with PBL. Subjects with very low belief can only fulfill 1 reasoning indicator well. Subjects with low belief can fulfill 3 reasoning indicators well and have not been able to fulfill 1 other indicator. Subjects with high belief can fulfill 4 indicators where 1 indicator is imperfect and subject with very high belief can fulfill all the indicators of reasoning well and complete.